(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
In order to support students in integrating information from the four disciplines, STEM education places a strong emphasis on using real-world contexts. The STEM Framework is a comprehensive STEM educational framework built around challenges that are protracted, persistent, and difficult. The knowledge and abilities needed to tackle those challenges must come from at least one dominant field, with the other disciplines contributing the techniques, procedures, or resources to aid in the process. This method can be used by teachers to create STEM lessons by identifying a central issue whose resolution calls for expertise from two or more STEM fields. The term “STEM education” is not new in the area, but due to pedagogical and curriculum issues, it is still not being taught in the classroom properly. In order to enable teachers to innovate and take charge of STEM education in their classroom, it is crucial to provide them with programs that assist them in applying and implementing STEM pedagogies in the classroom. To integrate STEM into practice, firstly we should identify the key elements of STEM. This study is conducted for addressing the major components of the STEM Education framework in Bangladesh perspective.